Long-term Complications and Treatment after Excision of Periocular Basal Cell Carcinoma – Case Report - Michalina Gałuszka; Dorota Pojda-Wilczek (Okulistyka)
Introduction Basal cell carcinoma is the most common malignant skin tumor, accounting for 90% of cases. The most important risk factors include age, male sex, skin phototypes I and II, frequent exposure to the sun, sunburn and positive family history of other skin tumors. More than 75% of basal cell carcinomas occur in the head and neck region. About 20% appear in the periocular region.